Atomic scale imaging of structural variations in La(1-x)/3LixNbO3 (0 ≤ x ≤ 0.13) solid electrolytes. (15th January 2017) - Hu, Xiaobing; Kobayashi, Shunsuke; Ikuhara, Yumi H.; Fisher, Craig A.J.; Fujiwara, Yasuyuki; Hoshikawa, Keigo; Moriwake, Hiroki; Kohama, Keiichi; Iba, Hideki; Ikuhara, Yuichi
Abstract: Solid-state Li-ion battery electrolyte materials La(1- x )/3 Li x NbO3 (LLNbO) are layered A-site-deficient perovskites with complex structural features resulting from their high intrinsic cation vacancy concentrations. We report an atomic-scale study of a series of single crystals of LLNbO with Li contents x  = 0, 0.04, 0.07, and 0.13 using state-of-the-art scanning transmission electron microscopy. By combining high angle annular dark field and annular bright field imaging techniques, columns of heavy and light atoms could be imaged simultaneously with atomic resolution. Structure modulation within La-rich layers, observed in all samples, was strongest for Li content x  = 0.07, the content which has been reported to exhibit the highest conductivity. Unlike for end member La1/3 NbO3 ( x  = 0), for Li content x  = 0.04, significant tilting of NbO6 octahedra occurs, with regions of different tilting directions corresponding to nanodomains within the crystal. This tilting and the associated nanodomains are absent when x  = 0.07, but occur again when x  = 0.13, with even greater distortion of NbO6 octahedra. These structural differences help explain the changes in Li-ion conductivity with Li content in LLNbO. Graphical abstract: Image 1